Early-life residential exposure to soil components in rural areas and childhood respiratory health and allergy - Devereux, Graham; Tagiyeva, Nara; Turner, Stephen W.; Ayres, Jon G.; Seaton, Anthony; Hudson, Gordon; Hough, Rupert L.; Campbell, Colin D.; Shand, Charles A. (The Science of the total environment, 2014)
The increase in asthma and allergies has been attributed to declining exposure to environmental microorganisms. The main source of these is soil, the composition of which varies geographically and which is a major component (40–45%) of household dust. Our hypothesis-generating study aimed to investigate associations between soil components, respiratory health and allergy in a Scottish birth cohort. The cohort was recruited in utero in 1997/8, and followed up at one, two and five years for the development of wheezing, asthma and eczema. Lung function, exhaled nitric oxide and allergic sensitization were measured at age five in a subset. The Scottish Soils Database held at The James Hutton Institute was linked to the birth cohort data by the residential postcode at birth and five years. The soil database contained information on size separates, organic matter concentration, pH and a range of inorganic elements. Soil and clinical outcome data were available for 869, 790 and 727 children at one, two and five years. Three hundred and fifty nine (35%) of children had the same address at birth and five years. No associations were found between childhood outcomes and soil content in the residential area at age five. The soil silt content (2–20μm particle size) of the residential area at birth was associated with childhood wheeze (adjusted OR 1.20, 95% CI [1.05; 1.37]), wheeze without a cold (1.41 [1.18; 1.69]), doctor-diagnosed asthma (1.54 [1.04; 2.28]), lung function (FEV1: beta −0.025 [−0.047;−0.001]) and airway inflammation (FENO: beta 0.15 [0.03; 0.27]) at age five, but not with allergic status or eczema. Whilst residual confounding is the most likely explanation for the associations reported, the results of this study lead us to hypothesise that early life exposure to residential soil silt may adversely influence childhood respiratory health, possibly because of the organic components of silt. •We have linked a birth cohort with the Scottish Soils Database.•We have looked for associations between asthma, allergy and soil content.•No associations found for soil content at residence at age 5years.•Silt content at birth residence adversely linked with respiratory health up to age 5.•Early life exposure to soil silt may adversely influence childhood respiratory health.